Leisure-Time Physical Activity and Cardiovascular Disease Risk Among Hypertensive Patients: A Longitudinal Cohort Study - Li, Jiqing; Zhang, Zhentang; Si, Shucheng; Xue, Fuzhong (Frontiers in Cardiovascular Medicine, 2021)
Objective: Few studies estimated the effect of leisure-time physical activity (LTPA) on cardiovascular diseases (CVD) risk among hypertensive patients in a longitudinal cohort. This study aims to evaluate the association between LTPA and cardiovascular diseases (CVD) in a longitudinal management cohort of hypertensive patients. Methods: A total of 58167 hypertensive patients without baseline CVD from a longitudinal cohort were included in this study. LTPA and other covariates were measured at the follow-up four times annually. The primary outcome was CVD events. The association between LTPA and CVD was assessed by the marginal structure model (MSM) and Cox model with adjustment for age, gender, BMI, smoking, drinking, diabetes, hyperlipidemia, and antihypertensive medication. The restricted cubic spline and segmented regression were used to assess the dose-response relationship between LTPA and CVD. Results: We recorded 16,332 CVD events, crude incidence of CVD were 89.68, 80.39, 62.64 and 44.04 per 1000 person-years for baseline 0,1-150,151-300,>300 min/week LTPA, respectively. Compared with inactive LTPA, the adjusted hazard ratios (HRs) estimated by Cox model and MSM-Cox model for CVD associated with 1-150,151-300, and 300 min/week LTPA were 0.85 (95% CI, 0.83–0.88), 0.67 (95% CI, 0.64–0.71), 0.47 (95% CI, 0.44–0.51), and 0.83 (95% CI, 0.76–0.91), 0.58 (95% CI, 0.52–0.63), 0.39 (95% CI, 0.35–0.44), respectively. Per 60 min/week increase of LTPA was associated with a 13% reduction of CVD risk. LTPA break-point was 417 min/week for CVD. Before and after the break-point, the slopes of the piecewise-linear relationship between LTPA and CVD risk were -0.0017 and -0.0003, respectively. Conclusion: LTPA was more strongly associated with the CVD risk than that estimated by conventional analyses based on baseline LTPA. 417 min/week is a breakpoint, after which, the incremental health benefits on CVD prevention obtained from the increase of LTPA are much less than before.